Human Service Administrators' Attitudes Toward Immigration: Shaped by Community and Organizational Context?. Issue 1 (1st January 2016) - Smith, Brenda D.; Womack, Bethany G.
Abstract : This study investigates whether human service administrators' attitudes toward immigration are associated with local demographic context. Hypotheses informed by threat, contact, and institutional theories are tested with a probability sample of human service administrators from Alabama, a state with pockets of dramatic growth in Latino immigrants. Results show that administrators from counties with larger percentage growth in the Latino population from 1990 to 2010 perceived a greater threat from immigration. Administrators perceived less threat from immigration when immigrant services were expected and legitimate in the organizational task environment. Results have implications for immigrant services in contexts of demographic change.